Off the hook - Green, John Patrick, 1975- (Green, John, 1975- InvestiGators (Series), 2021)
"The InvestiGators are the best crime-fighting duo in the world. But not even their hi-tech training programs can prepare them for the return of their greatest nemesis, Crackerdile, in a shocking new form! Even worse, he's creating a team of super villains! Faced with the choice between saving themselves or catching the crooks, can Mango and Brash make sure the gator good prevails?"--